2018
DOI: 10.1002/cbic.201800439
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Probes for the Epimerization Domain of Nonribosomal Peptide Synthetases

Abstract: Nonribosomal peptide synthetases (NRPSs) are responsible for the synthesis of a variety of bioactive natural products with clinical and economic significance. Interestingly, these large multimodular enzyme machineries incorporate nonproteinogenic d-amino acids through the use of auxiliary epimerization domains, converting l-amino acids into d-amino acids that impart into the resulting natural products unique bioactivity and resistance to proteases. Due to the large and complex nature of NRPSs, several question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Previously, pK a calculations indicated that the catalytic histidine residue was in a protonated state, suggesting that glutamate would act as a base in the epimerization mechanism. 14,18 This correlates with our data that in the wildtype TycA crosslinking, band A indicates 2.6 times more crosslinking than band B. For the H743A mutant crosslinking, where the catalytic residue E882 acts as a nucleophile, band A only shows 73% crosslinking compared to that of the wild-type crosslinking band A.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previously, pK a calculations indicated that the catalytic histidine residue was in a protonated state, suggesting that glutamate would act as a base in the epimerization mechanism. 14,18 This correlates with our data that in the wildtype TycA crosslinking, band A indicates 2.6 times more crosslinking than band B. For the H743A mutant crosslinking, where the catalytic residue E882 acts as a nucleophile, band A only shows 73% crosslinking compared to that of the wild-type crosslinking band A.…”
Section: Discussionsupporting
confidence: 88%
“…To further understand the roles of these active site residues, we decided to perform a diketopiperazine (DKP) assay, an in vitro condensation assay that allows us to indirectly study the activity of the E domain. 18,27 This assay allows us to quantify the dipeptide formed between the initiation module (TycA) and the subsequent downstream module TycB 1 (C-A-PCP Pro ), which is responsible for the selective uptake of epimerized D-Phe substrate in its condensation reaction. First, the A domains of TycA and TycB 1 catalyze the adenylation of L-Phe and L-Pro using ATP, and the activated amino acids are loaded onto their respective PCPs producing L-Phe-TycA and L-Pro-TycB 1 .…”
Section: E Domain Activity Assay -Dkp Assaymentioning
confidence: 99%
“…During reprotonation, an L/D mixture is obtained, but due to a strong specificity, the following C domain recognizes only the d -amino acids [ 91 ]. Different work is underway to shed light on the mechanism of action of these enzymes [ 92 ].…”
Section: Biosynthesismentioning
confidence: 99%
“…Similarly to NRPS, the synthesized PKs are modified by tailoring enzymes, such as ketoreductase, dehydratase, enoylreductase, or methyl transferase. The modifications often lead to increase in the bioactivity and the resistance of NRPs and PKs to enzymatic lysis [45]. They also generate large structural diversity within one class of compounds.…”
Section: Non-ribosomal Peptides (Nrps) and Polyketides (Pks)mentioning
confidence: 99%